Decomposing return and volatility connectedness in Northwest European gas markets: Evidence from the 𝑅² connectedness approach - Markos Farag; Oliver Ruhnau (Institute of Energy Economics at the University of Cologne (EWI), 2024)
Regulatory reforms by the European Commission have facilitated the integration of the European gas market, increasing interdependence in prices and associated risks across gas hubs. Recent external shocks, including the COVID-19 pandemic and the Russian invasion of Ukraine, have disrupted market interconnectedness, as evidenced in the literature. However, whether the nature of shock transmission-contemporaneous or delayed-changes during market instability, how quickly price and volatility connectedness recover afterward, and whether spot and futures prices are affected differently remain unclear. This paper analyzes the connectedness of natural gas hubs in Northwest Europe from 2020 to 2024 using the R2 decomposition connectedness method. Our findings show that contemporaneous spillovers dominate lagged ones, even during external shocks, indicating rapid market adjustments. Moreover, while market connectedness significantly decreased during major disruptions, it promptly returned to pre-crisis levels once these disruptions subsided. Regression results indicate a significant link between reduced market connectedness and pipeline congestion, particularly when combined with higher future price expectations. Futures markets showed higher connectedness than spot markets during tight conditions, suggesting alignment with broader expectations and reduced susceptibility to physical constraints.
Keywords: C11; C32; F14; L71; Q31; Q43; 330; European Natural gas market; Dynamic linkages; R2 decomposition; volatility